Sevilla, refugio creativo. - Castro-Higueras, Antonio; Navarro-Ardoy, Luis; Pérez-Rufi, José Patricio; Carballeda-Camacho, Mireya Rocío (Universidad de Málaga, 2024)
"SEVILLA, a creative refuge" is a documentary that explores a creative ecosystem located in the northeast quadrant of Seville's historic center.
Keywords: Barrios - Sevilla; Industria cultural - Sevilla; distritos creativos; Sevilla; cultura; industrias creativas